2019
DOI: 10.1111/sltb.12585
|View full text |Cite
|
Sign up to set email alerts
|

Proximal Correlates of Suicidal Ideation and Behaviors: A Test of the Interpersonal‐Psychological Theory of Suicide

Abstract: Objective The interpersonal‐psychological theory of suicide hypothesizes proximal causes of suicidal ideation and behaviors; however, past studies have generally tested distal relations. The present study tested the proximal nature of the theory’s hypotheses. Methods A repeated‐measures design collected daily survey data on the theory constructs over 90 days from 206 (150 women) college students with previous histories of suicidal ideation. Participants completed 7,342 (39.6%) of the 18,540 surveys sent. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 46 publications
0
20
1
1
Order By: Relevance
“…The results of these studies were mixed, with four studies not finding a statistically significant interaction (Miller et al, 2016;Roeder & Cole, 2018;Teismann et al, 2017;Yang et al, 2020), and six studies finding a statistically significant interaction. Of the six studies that found a significant interaction, one indicated a pattern contrary to the synergy hypothesis (i.e., the relationship between thwarted belongingness and suicide ideation was weaker among those with high levels of perceived burdensomeness; Batterham et al, 2018), whereas five studies found an interaction with a pattern that was consistent with the synergy hypothesis (i.e., the relationship between thwarted belongingness and suicide ideation was stronger among those with high levels of perceived burdensomeness; Czyz et al, 2018;Hallensleben et al, 2019;Kleiman et al, 2014;Kyron et al, 2018;Wolford-Clevenger et al, 2019). Of note, the majority of the studies that found a pattern consistent with the synergy hypothesis used shortterm follow-up intervals (e.g., daily or multiple within-day measurements; Czyz et al, 2018;Hallensleben et al, 2019;Kyron et al, 2018;Wolford-Clevenger et al, 2019), while all the studies that found a pattern inconsistent with the synergy hypothesis used extended follow-up intervals (i.e., three months -four years; Batterham et al, 2018;Miller et al, 2016;Roeder & Cole, 2018;Teismann et al, 2017;Yang et al, 2020).…”
Section: Longitudinal Examination Of the Synergy Hypothesismentioning
confidence: 89%
See 2 more Smart Citations
“…The results of these studies were mixed, with four studies not finding a statistically significant interaction (Miller et al, 2016;Roeder & Cole, 2018;Teismann et al, 2017;Yang et al, 2020), and six studies finding a statistically significant interaction. Of the six studies that found a significant interaction, one indicated a pattern contrary to the synergy hypothesis (i.e., the relationship between thwarted belongingness and suicide ideation was weaker among those with high levels of perceived burdensomeness; Batterham et al, 2018), whereas five studies found an interaction with a pattern that was consistent with the synergy hypothesis (i.e., the relationship between thwarted belongingness and suicide ideation was stronger among those with high levels of perceived burdensomeness; Czyz et al, 2018;Hallensleben et al, 2019;Kleiman et al, 2014;Kyron et al, 2018;Wolford-Clevenger et al, 2019). Of note, the majority of the studies that found a pattern consistent with the synergy hypothesis used shortterm follow-up intervals (e.g., daily or multiple within-day measurements; Czyz et al, 2018;Hallensleben et al, 2019;Kyron et al, 2018;Wolford-Clevenger et al, 2019), while all the studies that found a pattern inconsistent with the synergy hypothesis used extended follow-up intervals (i.e., three months -four years; Batterham et al, 2018;Miller et al, 2016;Roeder & Cole, 2018;Teismann et al, 2017;Yang et al, 2020).…”
Section: Longitudinal Examination Of the Synergy Hypothesismentioning
confidence: 89%
“…Despite the abundance of cross-sectional studies testing the main tenets of the Interpersonal Theory of Suicide, to date, only ten longitudinal studies have tested the synergy hypothesis (Batterham et al, 2018;Czyz et al, 2018;Hallensleben et al, 2019;Kleiman et al, 2014;Kyron et al, 2018;Miller et al, 2016;Roeder & Cole, 2018;Teismann et al, 2017;Wolford-Clevenger et al, 2019;Yang et al, 2020). The results of these studies were mixed, with four studies not finding a statistically significant interaction (Miller et al, 2016;Roeder & Cole, 2018;Teismann et al, 2017;Yang et al, 2020), and six studies finding a statistically significant interaction.…”
Section: Longitudinal Examination Of the Synergy Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…Passend dazu präsentiert sich die Befundlage zur Dreifachinteraktion von PB, TB und allgemeiner Hoffnungslosigkeit hinsichtlich der Vorhersage von aktiven Suizidgedanken als heterogen mit stützenden [z.B. Hagan et al, 2015;Talley et al, 2016;Wolford-Clevenger et al, 2019] als auch widersprechenden Befunden [z.B. Christensen et al, 2013;Baertschi et al, 2017;Forkmann et al, 2021;Rath et al, 2021].…”
Section: Interpersonale Theorie Suizidalen Verhaltensunclassified
“…A thwarted sense of belongingness has been identified in the Interpersonal Psychological Theory of Suicide (hereafter Interpersonal Theory; Joiner, 2005), as one element necessary for suicidal ideation (alongside the perception of being a burden — which is not a focus of the present paper; Joiner, 2005; Van Orden et al, 2010). Recent research has identified different profiles of suicidal ideation over time, based on temporal trajectories of risk factors such as belongingness (Bagge et al, 2017; Kyron et al, 2018; Kyron, Badcock, et al, 2019; Kyron, Hooke, et al, 2019; Rogers & Joiner, 2019; Wolford‐Clevenger et al, 2020). Importantly, these studies explored these profiles in a variety of age groups, clinical, and community cohorts, and largely focused on the dual contribution of belongingness and perceived burdensomeness.…”
Section: Introductionmentioning
confidence: 99%